1999
DOI: 10.1088/0022-3727/32/11/305
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetoresistance in electrodeposited Co87Fe13/Cu compositionally modulated alloys

Abstract: In this paper we report on the giant magnetoresistance effect and oscillatory exchange coupling in electrodeposited Co 87 Fe 13 /Cu compositionally modulated alloys. The alloys are compositionally modulated over nanometre length scales with ferromagnetic Co 87 Fe 13 (Cu) alloy layers and non-magnetic Cu layers. Co 87 Fe 13 /Cu multilayered thin films were electrodeposited from a single sulfate plating solution containing all metallic ions of interest under computer-controlled potentiostat switching on (111)-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
1
21
1
Order By: Relevance
“…This means that a strong dissolution of the magnetic layer took place during the Cu deposition pulse and, thus, for each multilayer, the actual magnetic layer thicknesses were less than the nominal preset value and the reverse is true for the Cu layer. According to our previous experience with ED Co/Cu multilayers, 13,26 at the Cu deposition potential applied by Kakuno et al, 9 the layer thickness changes due to the magnetic layer dissolution during the Cu deposition pulse may be around 1 nm. This is especially important since the major objective of Kakuno et al 9 was to study the dependence of GMR on the Cu layer thickness.…”
Section: Comparison Of Gmr Behavior With Previously Investigated Ed Fmentioning
confidence: 89%
See 3 more Smart Citations
“…This means that a strong dissolution of the magnetic layer took place during the Cu deposition pulse and, thus, for each multilayer, the actual magnetic layer thicknesses were less than the nominal preset value and the reverse is true for the Cu layer. According to our previous experience with ED Co/Cu multilayers, 13,26 at the Cu deposition potential applied by Kakuno et al, 9 the layer thickness changes due to the magnetic layer dissolution during the Cu deposition pulse may be around 1 nm. This is especially important since the major objective of Kakuno et al 9 was to study the dependence of GMR on the Cu layer thickness.…”
Section: Comparison Of Gmr Behavior With Previously Investigated Ed Fmentioning
confidence: 89%
“…By properly decomposing the GMR into FM and SPM contributions, it could be concluded that the GMR FM contribution does not exhibit an oscillatory GMR in ED Fe-Co/Cu multilayers as a function of the spacer layer thickness, in agreement with previous observations on various ED multilayers. [28][29][30][31][32][33][34][35] By a detailed analysis of the results of Kakuno et al 9 about an oscillatory GMR, it could be pointed out that their findings cannot be considered as reliably demonstrating such a behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the coupling between adjacent layers has to be lower to obtain GMR in the lower magnetic field such as multilayers and spin valves. For the CoFe/Cu multilayers produced by the electrodeposition, there are some reports on the dependence of their GMR and its sensitivity on ferromagnetic or non-magnetic layers thicknesses [8,[14][15][16][17][18][19][20][21]. Non-magnetic layer dependence of deposition potential were studied by Toth et al [8].…”
Section: Introductionmentioning
confidence: 99%